Use of Montmorillonite Clay and Flocculating Bacteria for Acid Mine Drainage Bioremediation - BIDAYAH (NIM : 13014011) - MOCH AGUNG GUNANDAR (NIM : 13014035), SAADATUL
Geologically, coal mines in Indonesia, particularly in Kalimantan, are characterized by high clay content (i.e., montmorillonite clays), thus leading to naturally occurring colloidal particles (a particle size of ~5 nm to ~1 Ã‚Âµm) in natural water systems. These colloids as particulate contaminants impart a colour to the water, which bring about increased turbidity and total suspended solids (TSS) concentration, therefore causing water pollution and ecological damages. In addition to coal mine activities, acid mine drainage (AMD) that are enriched with large amounts of sulphate, iron, and heavy metals, have long been recognized to occur at coal mine sites, causing them to be of greater environmental concern as well. Hence, the complex problems of environmental contamination in coal mine sites need to be overcome by establishing an efficient, cost-effective, eco-friendly treatment. The main objective of the present work was to study the utilization of montmorillonite to remediate highly contaminated AMD as well as two flocculating bacteria, which are Alicyclobacillus ferrooxydans SKC/SAA-2 and Citrobacter youngae SKC-4 to enhance destabilization of colloidal montmorillonite suspensions. A series of experiments and analyses were carried out including adsorption test, flocculation test, settling test, FTIR and SEM-EDS analyses.Experimental results showed that the AMD or simulated-AMD in contact with montmorillonite clays resulted in an increase in pH, high removals of ferric iron (Fe3+) that reach about 98% and, in 30 minutes of settling, TSS removal up to 92%. In addition, colloidal montmorillonite suspensions successfully flocculated with flocculating bacteria alone, but the highest removal of TSS in AMD ensued when the flocculating bacteria were absent.